2000
DOI: 10.1021/ic9905897
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Insulin-Mimetic Properties of Bis(acetylacetonate)oxovanadium(IV) and Derivatives1

Abstract: The syntheses and the solid state structural and spectroscopic solution characterizations of VO(Me-acac)2 and VO(Et-acac)2 (where Me-acac is 3-methyl-2,4-pentanedionato and Et-acac is 3-ethyl-2,4-pentanedionato) have been conducted since both VO(acac)2 and VO(Et-acac)2 have long-term in vivo insulin-mimetic effects in streptozotocin-induced diabetic Wistar rats. X-ray structural characterizations of VO(Me-acac)2 and VO(Et-acac)2 show that both contain five-coordinate vanadium similar to the parent VO(acac)2. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(112 citation statements)
references
References 59 publications
9
99
2
Order By: Relevance
“…However, at pharmacological concentrations, some species are potential therapeutic agents [3,4]. Thus, the insulin-enhancing, insulin mimetic properties of oxovanadium(V) complexes, their use as model complexes for the active site of vanadoenzymes, and their use as catalysts in biological and industrial processes have been reported [5][6][7][8][9]. Furthermore, these compounds exhibit potential as anti-tumour agents by inhibiting growth of malignant cell lines by induction of cell-cycle arrest and/or cytotoxic effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, at pharmacological concentrations, some species are potential therapeutic agents [3,4]. Thus, the insulin-enhancing, insulin mimetic properties of oxovanadium(V) complexes, their use as model complexes for the active site of vanadoenzymes, and their use as catalysts in biological and industrial processes have been reported [5][6][7][8][9]. Furthermore, these compounds exhibit potential as anti-tumour agents by inhibiting growth of malignant cell lines by induction of cell-cycle arrest and/or cytotoxic effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that BSA does not interfere with the inhibition measurements. VO(acac) 2 , VO(Clacac) 2 , and VO(Benzac) 2 were reported to maintain their integrity in solution whereas VO(Meacac) 2 is immediately oxidized to a vanadium(V) species [18]. UV-visible spectral data for the VO(b-diketone) 2 complexes used in the present study were obtained on a Hewlett-Packard model 8453 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…VO(acac) 2 , bis(acetylacetonato)oxovanadium(IV), and VO(Meacac) 2 , bis(3-methylacetylacetonato)oxovanadium(IV), Figure 1, as well as bis (3-ethylacetylacetonato)oxovanadium(IV) function as insulin-enhancing agents, lowering blood glucose levels of streptozocin-induced rats and increasing glucose uptake by 3T3-L1 adipocytes [16,17,18]. Katoh and co-workers demonstrated a correlation between the insulin-mimetic activity of vanadyl-hydroxythiazolethione complexes and the Hammett parameter for a substituent group on the ligand, however, very few such structure-activity relationships have been reported [19].…”
Section: Introductionmentioning
confidence: 99%
“…X-ray crystallography of 1 shows only the trans isomer in the solid state. Experimental evidence by ENDOR [28] and EPR [30] points to the formation of only the trans isomer of V IV O(acac) 2 in solution, but some authors argue the cis form may also exist [9,7,32].…”
Section: Mechanism and Nature Of The Active Species For Dna Cleavagementioning
confidence: 99%
“…The complex V IV O(Etmaltolato) 2 has successfully completed phase II of human clinical trials [5,6] and became a benchmark drug candidate in this field. The V IV -complex vanadyl(acetylacetonate), V IV O(acac) 2 , has been reported to have therapeutic properties, and this has attracted much interest in its biological behaviour [7,8]. It has been proposed as a particularly efficient insulin-enhancing compound [9], and a recent study [10] focused on its anticancer potential and mechanism of action in a human hepatoma cell line, V IV O(acac) 2 being found to block the cell cycle permanently at the G1 phase on HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%